“Beggaring the Nation”: Bodily Inscription and the Body Politic in Rohinton Mistry’s A Fine Balance - Johnson, James W. (Studies in Canadian Literature, 2015)
In Rohinton Mistry’s novel A Fine Balance (1995), the ubiquity of bodily metaphor and description reveals a fundamental concern with the representational capacity of the body. Set in India and focussing primarily on the volatile period of the Emergency (1975-1977), the novel explores the way in which historical and political processes impinge upon the lives of, and inscribe the bodies of, individual citizens. In addition to providing a structural paradigm by charting the progression of the narrative, images of bodily decline, deterioration, and mutilation serve as signifiers of the violent regulatory practices of both the caste-system and the Indira Gandhi regime during the Emergency. Within a theoretical framework informed by the work of Michel Foucault, Julia Kristeva, and others, the regulatory practices of the state in A Fine Balance can be understood to produce not only docile bodies that are useful and obedient, but also abject bodies that disturb the coherence and stability of a social structure depicted as a healthy and pure body. Mistry’s representations of the body as an inscriptive surface thus problematize the attempts of the novel’s ruling Indira Gandhi regime to depict the Indian body politic as a coherent, homogenous, and corporeal totality. Ultimately, A Fine Balance suggests that it is only through an awareness of the diffuse interrelationships between individual subjects that we can begin to imagine the complex and heterogeneous network of linkages of which the nation is comprised.